A new era of spectroscopy: SINFONI, NIR integral field spectroscopy at the diffraction limit of an 8m telescope - Mengel, S; Eisenhauer, F; Tecza, M; Thatte, N; Roehrle, C; Bickert, K; Schreiber, J (2000)
SINFONI, the SINgle Faint Object Near-infrared Investigation, is an instrument for the Very Large Telescope (VLT), which will start its operation mid 2002 and allow for the first time near infrared (NIR) integral field spectroscopy at the diffraction limit of an 8-m telescope. SINFONI is the combination of two state-of-the art instruments, the integral field spectrometer SPIFFI, built by the Max-Planck-Institut fuer extraterrestrische Physik (MPE), and the adaptive optics (AO) system MACAO, built by the European Southern Observatory (ESO). It will allow a unique type of observations by delivering simultaneously high spatial resolution (pixel sizes 0.025arcsec to 0.25arcsec) and a moderate spectral resolution (R~2000 to R~4500), where the higher spectral resolution mode will allow for software OH suppression. This opens new prospects for astronomy.